Effective Methanol Oxidation with Platinum Nanoparticles-Decorated Poly(2-bromomethyl-2-methyl-3, 4-propylenedioxythiophene)-Coated Glassy Carbon Electrode. Issue 8 (13th August 2021) - Karazehir, Tolga; Sarac, Baran; Gilsing, Hans-Detlev; Eckert, Jürgen; Sarac, A. Sezai
Abstract : Here, we developed a porous network of bromomethyl-substituted 3, 4-propylenedioxythiophene polymer using a simple and efficient technique of electrochemical deposition used as conductive support for methanol oxidation. Platinum nanoparticles (PtNPs) are well dispersed and decorated on a high surface area of electrochemically deposited Poly(2-bromomethyl-2-methyl-3, 4-propylenedioxythiophene (PProDOT-Br) on a glassy carbon electrode (GCE). A thin film of PProDOT-Br acts as a supporting matrix for deposition of PtNPs and improves the interfacial properties between electrode and electrolyte. The PtNPs-decorated PProDOT-Br (Pt/PProDOT-Br) samples were characterized by X-ray diffraction, Fourier transform infrared attenuated total reflectance spectroscopy, atomic force microscopy, and scanning electron microscopy. Furthermore, the electrocatalytic performance of Pt/PProDOT-Br on GCE for methanol oxidation was assessed by cyclic voltammetry, chronoamperometry, and electrochemical impedance spectroscopy measurements. The findings suggest that the use of Pt/PProDOT-Br/GCE assemblies for efficient methanol oxidation in alkaline media with a small intermediate poisoning is promising for applications as anode material in DMFCs, which should be attributed to the PProDOT-Br support providing a larger surface area with porous nature and enabling the adsorption of more CH3 OH for further oxidation. The developed porous network PProDOT-Br with high capacitance may also have large potential in supercapacitor applications.